Komparasi Kinerja Keuangan Bank Syariah Indonesia dan Bank Syariah Malaysia Pada Masa Pandemi Covid-19 - Yoga Raunaqa; Dea Al Risna Deva; Kharis Fadlullah Hana (Shafin: Sharia Finance and Accounting Journal, 2022)
Abstract: Financial performance is an important factor for maintaining the health of banks, but the Covid-19 has greatly impacted the economic sector, one of which is banking. The purpose of this study was to find out how the financial performance of Bank Syariah Indonesia and Bank Maybank Berhard Malaysia in 2020-2021 during the covid 19 pandemic. The method used in this study was a quantitative method using descriptive analysis and financial ratio analysis tools, namely the independent paired T-test. The data collection technique is to collect secondary data in the form of an annual report (annual hassle) of financial performance during the COVID-19 pandemic published by the Indonesian Islamic bank or the Financial Services Authority (OJK) and the official website of the Islamic bank Maybank Islamic Berhad Kuala Lumpur. The results showed that there was no significant difference in the financial performance of Indonesian Islamic banks and Malaysian banks with maybanks from the financial ratios of CAR, ROA, ROE, FDR, NPF, and BOPO during the COVID-19 pandemic from 2020-2021. The results of this study provide recommendations that the management of Indonesian Islamic banks and Malaysian banks maybank hard to be able to maintain and further improve their already good financial performance. Keywords: Comparison, Financial Performance, Covid 19 Abstrak: Kinerja keuangan merupakan faktor yang penting untuk mejaga kesehatan bank, tetapi dengan adanya covid-19 ini sangat berdampak pada sektor ekonomi salah satunya perbankan . tujuan penelitian ini adalah untuk mengetahui bagaimana kinerja keuangan Bank Syariah Indonesia dan Bank Maybank Berhard Malaysia tahun 2020-2021 pada masa pandemi covid 19. Metode yang digunakan dalam penelitian yaitu metode kuantitatif dengan menggunakan analisis deskriptif dan alat analisis rasio keuangan yaitu uji independent paired T-test. Teknik perolehan data yaitu mengumpulkan data-data sekunder yang berupa laporan tahunan (annual repot) kinerja keuangan selama pandemi covid-19 yang diterbitkan oleh bank syariah Indonesia atau Otoritas Jasa Keuangan (OJK) dan website resmi bank syariah Maybank Islamic Berhad Kuala lumpur. Hasil penelitian menunjukkan bahwa tidak terdapat perbedaan yang signifikan kinerja keuangan bank syariah Indonesia dan bank maybank berhard Malaysia dari rasio keuangan CAR, ROA, ROE,FDR, NPF, dan BOPO selama masa pandemi covid 19 dari tahun 2020-2021. Hasil penelitian ini memberikan rekomendasi bahwa manajemen bank syariah Indonesia dan bank maybank berhard Malaysia untuk dapat mempertahankan dan lebih meningkatkan kinerja keuangannya yang sudah baik. Kata Kunci: Perbandingan, Kinerja keuangan, Covid 19